What is a Dictionary? - Henning Bergenholtz (Woordeboek van die Afrikaanse Taal-WAT, 2012)
By comparing different definitions in dictionaries and in theoretical papers we know that lexicographers have very different opinions on the topic: "What is a dictionary?" We see too that lexicographic tools with the same type of content sometimes are called dictionary, sometimes encyclopedia, sometimes lexicon. In reality it is not a large problem if the information in a certain tool is of a high quality as to the intended function. Nevertheless I will give not one but two additional definitions of two different types of information tools. There will also be a discussion on the relevance for the concept of dictionary in connection with the research registration in universities.